1991
DOI: 10.1073/pnas.88.1.199
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between amount of virus with altered nucleotide sequence and the monkey test for acceptability of oral poliovirus vaccine.

Abstract: Production of live attenuated oral poliomyelitis vaccine (OPV) requires rigorous neurovirulence safety testing of each vaccine lot, currently carried out in monkeys. It has been reported that a change from 472-U to 472-C in the type 3 OPV RNA is associated with an increased histologic lesion score produced upon intraspinal inoculation of the mutant virus in monkeys. We have developed a method, based on polymerase chain reaction, for measuring the relative abundance of these mutant sequences directly in vaccine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(89 citation statements)
references
References 17 publications
2
86
0
1
Order By: Relevance
“…This characteristic has importance for live attenuated viral vaccines, in which the presence or relative abundance of mutant virus variants can affect both phenotypic and physiopathologic features (4) and the diversity of immunologic responses in vaccine recipients. For instance, neurovirulence of oral poliovirus vaccine (OPV) is often determined by the presence of a tiny fraction of mutant viral particles in an overwhelming excess of non-neurovirulent virus (5). Genetic stability is therefore a required characteristic of live attenuated viral vaccines and is of particular importance for new vaccines derived by targeted genetic manipulations and cloning.…”
Section: Neurobiologymentioning
confidence: 99%
See 1 more Smart Citation
“…This characteristic has importance for live attenuated viral vaccines, in which the presence or relative abundance of mutant virus variants can affect both phenotypic and physiopathologic features (4) and the diversity of immunologic responses in vaccine recipients. For instance, neurovirulence of oral poliovirus vaccine (OPV) is often determined by the presence of a tiny fraction of mutant viral particles in an overwhelming excess of non-neurovirulent virus (5). Genetic stability is therefore a required characteristic of live attenuated viral vaccines and is of particular importance for new vaccines derived by targeted genetic manipulations and cloning.…”
Section: Neurobiologymentioning
confidence: 99%
“…Development of new methods for rapid analysis of viral nucleic acids, with emphasis on quantitative characterization of mutation profiles, is important for improving vaccine consistency and safety. Previously, we have developed a very sensitive method called mutant analysis by PCR and restriction enzyme cleavage (MAPREC) (5). By using this technique, we showed that even a small increase in the content of certain revertants in OPV batches, from levels around 0.5% to slightly over 1%, results in vaccine lot failure in the monkey neurovirulence test and makes the batch unacceptable for use in humans Abbreviations: MAPREC, mutant analysis by PCR and restriction enzyme cleavage; MALDI-TOF, matrix-assisted laser desorption͞ionization time-of-flight; OPV, oral poliovirus vaccine; CEF, chicken embryo fibroblast.…”
Section: Quantitative Mutant Analysis Of Viral Quasispecies By Chip-bmentioning
confidence: 99%
“…These mutations have been identified in Sabin type 3 poliovirus (472U→C) (Cann et al, 1984), as well as type 2 (481A→G) (Macadam et al, 1993), and type 1 (480G→A and 525U→C) (Otelea et al, 1993); they are believed to selectively affect initiation of translation of viral polyprotein in neuronal cells (Guest et al, 2004;Svitkin et al, 1990). Previously was shown that the content of these revertants www.intechopen.com Viral Genomes -Molecular Structure, Diversity, Gene Expression Mechanisms and Host-Virus Interactions 188 was low in vaccine batches that failed the monkey neurovirulence test (Chumakov et al, 1991). Sensitive mutant analysis by PCR and restriction enzyme cleavage (MAPREC) method is used to monitor the quantity of neurovirulent revertants in batches of oral poliovirus vaccine (Chumakov et al, 1991).…”
Section: Microarray Assay For Quantitation Of Known Virulent Mutationsmentioning
confidence: 99%
“…That occurred with pSPBNGA-GA, a live rabies virus recombinant vaccine candidate, which was obtained via reverse genetics (Dietzschold et al, 2004). Additionally, it was demonstrated that some deletions in HIV-1 vaccine strains can evolve into fast-replicating variants by multiplication of remaining sequence motifs, and their safety is therefore not guaranteed (Berkhout et al, 1999), and the presence of even a small fraction of viral mutants in an oral poliovirus vaccine can have negative effect on its safety (Chumakov et al, 1991), suggesting that genetic consistency must be carefully monitored to ensure that accumulated mutants do not adversely impair the safety and efficacy of the vaccine.…”
mentioning
confidence: 99%
“…Enumerating all of the milestones reached in PV studies is far beyond the scope of this review, however, this list would include sequencing of the PV genome (9,10), the development of reverse genetics for the virus (11), elucidation of the crystal structure of the virion (12), identification of the internal ribosomal entry site (IRES) (13), identification of the PV receptor (PVR, CD155) (14,15), development of a transgenic mouse model of poliomyelitis (16,17), identification of attenuation determinants in oral polio vaccine (OPV) strains (18,19), identification of drug candidates (20,21), development of a cell-free replication system (22), identification of cis-acting replication elements (23,24), identification of circulating vaccine-derived PVs (cVDPVs) (25), and identification of host targets for drug candidates (26)(27)(28)(29)(30). PV studies in the post-vaccine era have produced valuable tools and information essential to the eradication program, including nucleotide sequences of PV and other enteroviruses (9,10,31), which have been used to design primers for current reverse transcription (RT)-PCR systems for PV detection (32,33); neurovirulence determinants of PV that are used for quality control of vaccines and evaluations of environmental isolates (18,34,35); PV-sensitive murine cell line (L20B) (14), which is a cell line that expresses the PVR and is currently used for PV surveillance because of its high specificity for PV infection, a PVR-transgenic mouse (TgPVR21) model as an alternative to monkeys used in neurovirulence tests for PV vaccines (36), and candidate compounds for antivirals, including V-073 (37).…”
Section: History Of Polio Virology and The Polio Eradication Programmentioning
confidence: 99%